Penggunaan Scaffold Kitosan-Aloe Vera Terhadap Proliferasi Sel Fibroblas pada Penyembuhan Luka Pasca Pencabutan Gigi Cavia Cobaya - Sularsih Sularsih; Fitria Rahmitasari (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2018)
Aloe vera has been investigated potential use in tissue engineering. Its bioactive compounds interact with growth factor receptor on the fibroblast and stimulate cells proliferation. The aim of this study was to investigate the proliferation of fibroblast cells on wound healing process of Cavia cobaya dental extraction using scaffold combination chitosan and Aloe vera. Cavia cobaya male with 300-350 grams of weight and in the age of 3 to 3.5 months. It divided into ten groups (n=5). For Treatment groups, Aloe vera scaffold(Av); Chitosan Scaffold (Ch); Scaffold combination chitosan-Aloe vera (Ch-Av) and scaffold combination chitosan- Aloe vera- hidroksiapatit(Ch-Av-HA) were applied into the socket of dental extraction. For control group, which were not given scaffold. Cavia cobaya were decaputated at 7 and 14 days and the jaw in the treated regions and control group were cut for Histopatology Anatomy examination to investigate the proliferation of fibroblast cells. Data were analyzed using One way Anova test. The proliferation of fibroblast cells were found higher in the group which given Av-Ch and Av-Ch-HA scaffold. The result showed significant differences in proliferation of fibroblast cells for 7 and 14 days observation compared to control group (p<0,05). The application of scaffold combination Chitosan and Aloe vera accelerate the wound healing process of Cavia cobaya dental extraction.